Graft-Recipient Anteroposterior Mismatch Does Not Affect the Clinical Outcomes of Osteochondral Allograft Transplantation of the Femoral Condyle. Issue 7 (30th July 2018) - Coxe, Francesca R.; Wang, Dean; Balazs, George Christian; Chang, Brenda; Jones, Kristofer J.; Rodeo, Scott A.; Williams, Riley J.
Objectives: For the treatment of femoral condyle cartilage defects, anteroposterior (AP) and mediolateral (ML) dimension matching in osteochondral allograft transplantation (OCA) pairs donor and recipient condyles to minimize articular incongruity. This aims to reduce the potential risk of graft failure and improve clinical outcomes. However, size matching restricts the number of compatible osteochondral allografts, which has a number of disadvantages including delayed surgical treatment and prolonged graft storage. Some surgeons match donor-to-recipient exclusively using the ML dimension to ensure that an adequately sized dowel can be harvested, while ignoring AP mismatch. Because a large AP mismatch can lead to radius of curvature differences between graft and host and potential articular incongruity after implantation, this study aimed to evaluate the association between AP mismatch and clinical outcomes of OCA. Methods: A retrospective review of patients treated with OCA for femoral condyle cartilage defects from 2000 to 2015 was conducted. A minimum follow-up of 2 years was required for analysis. Graft characteristics, including AP and ML dimensions, were gathered from vendor-specific allograft offering documents. Patient condyle dimensions were measured from preoperative magnetic resonance imaging (Figure 1). Reoperations and patient responses to validated outcome measures were reviewed. Failure was defined by any partial removal/revision of the allograft or conversion to knee arthroplasty. A multivariable logistic regression model was fitted to examine the association of AP mismatch with OCA failure while adjusting for patient age, sex, number of previous ipsilateral knee surgeries, and number of lesions treated. Results: A total of 69 knees (mean age, 35.7 years) met the inclusion criteria. Mean duration of follow-up was 4 years (range, 2-16 years). The average absolute AP mismatch between graft and patient was 6.7 mm (range, 0-20 mm) (P <0.01). In contrast, the average absolute ML mismatch between graft and patient was 2.3 mm (range, 0-10 mm) (P = 0.33). At final follow-up, 19 knees had failed. There was no significant difference in the average absolute AP mismatch between failures (8.1 mm) and non-failures (6.2 mm) (P = 0.17). Multivariate logistic regression revealed that AP mismatch was not associated with graft failure (P = 0.15) (Table 1). At final follow-up, clinically significant improvements were noted in the pain (52.0 to 73.2) and physical functioning (60.1 to 80.1) subscales of the Short Form-36 (P <0.01 for both), International Knee Documentation Committee subjective form (47.8 to 65.9; P <0.01), and Knee Outcome Survey-Activities of Daily Living (64.2 to 82.0; P <0.01). Conclusion: OCA has consistently shown excellent long-term results in patients, including high-level athletes, with large chondral defects. Widespread use of OCA, however, is limited by the practice of procuring an appropriately sized allograft that matches the recipient hemicondyle in ML and AP dimensions. The results of the present study show no association between the magnitude of graft-patient AP mismatch and OCA failure. Most importantly, patient-reported outcome measures improved significantly over the course of follow-up, despite a wide range of AP mismatch between graft and patient. Our results suggest that AP length matching within the limits measured here is not a contraindication for graft acceptance.